Freestanding Triboelectric-layer Mode Triboelectric Nanogenerator (TENG) via Rotating Circle - Lee, Lini; Abd Elnabi, Khaled (International Journal of Integrated Engineering, 2024)
In a Triboelectric Nanogenerator (TENG), electricity can be harvested by utilizing an electrostatic charge between two triboelectric materials. This project focused on optimizing the output power of a TENG using mini lathe beads machine for a freestanding triboelectric-layer mode via rotating circle. The TENG is constructed using aluminum electrodes, adhered to Teflon (PTFE) on one side while the other rotational side is constructed using different triboelectric layers. The materials used on the rotational side include Teflon, silicone rubber, fiberglass, polyvinyl chloride (PVC) and Neoprene rubber. These materials are prepared in a circular shape, with a diameter of 50 mm and thickness that varied from0.13 mm to 2 mm depending on the material employed. These materials are shown to be able to produce voltages ranged from 2.5 V to 18 V, while Neoprene Rubber showed the highest output at 35.02 V. Based on the experimental work, there are several factors that can affect the performance of the TENG, including temperature, size, material durability, rotating speed, and force as well as alignment of the two layers. This project can be implemented to harvest energy from a moving object like the rotation disc structure, such as a moving automobile or a train.